2019
DOI: 10.1039/c9md00295b
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of napabucasin derivatives for the treatment of tuberculosis

Abstract: Thirty-one napabucasin derivatives were synthesized and evaluated for their antitubercular activities, as well as for studying the structure–activity relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Previous studies reported the antibacterial activity of 2-acetylfuro-1,4-naphathoquinone against Escherichia coli , Streptococcus faecalis , and Staphylococcus aureus [ 15 , 17 ]. A recent study also showed its antimycobacterial activity for the treatment of tuberculosis [ 18 ]. In addition, the NAP is in phase III clinical trials for the treatment of cancers (i.e., gastric cancer, pancreatic cancer, and colorectal cancer) [ 19 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported the antibacterial activity of 2-acetylfuro-1,4-naphathoquinone against Escherichia coli , Streptococcus faecalis , and Staphylococcus aureus [ 15 , 17 ]. A recent study also showed its antimycobacterial activity for the treatment of tuberculosis [ 18 ]. In addition, the NAP is in phase III clinical trials for the treatment of cancers (i.e., gastric cancer, pancreatic cancer, and colorectal cancer) [ 19 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The residue was purified by chromatography on a silica gel column with PE-EA to give pure intermediate 12a (4.9 g, 75%). 1 H NMR (400 MHz, DMSO-d 6 ) δ 8.17 General Procedures for the Synthesis of Intermediates 14a−14l. Intermediate 13a (4.0 g, 13.0 mmol, 1.0 equiv) was added to 30 mL solution of EtOH/H 2 O (v/v, 3/1).…”
Section: Synthesis Of Tert-butyl 4-(4-amino-5-isopropoxy-2methylpheny...mentioning
confidence: 99%
“…1 H NMR (400 MHz, DMSO-d 6 ) δ 10.73 (s, 1H), 9.32 (s, 3H), 8.41 (s, 1H), 7.60 (s, 1H), 7.48 (s, 1H), 7.38 (d, J = 8.3 Hz, 1H), 7.22 (t, J = 8.1 Hz, 1H), 7.06 (dd, J = 7.9, 1.1 Hz, 1H), 6.94 (s, 1H), 4.58−4.48 (m, 1H), 3.36 (d, J = 11.9 Hz, 2H), 3.14−2.95 (m, 3H), 2.26 (s, 3H), 2.12−1.95 (m, 2H), 1.83 (d, J = 12.9 Hz, 2H), 1.21 (d, J = 6.0 Hz, 6H). 13 1 H NMR (400 MHz, DMSO-d 6 ) δ 8.93 (s, 1H), 8.15 (s, 1H), 8.03 (s, 1H), 7.74 (s, 1H), 7.67 (d, J = 2.4 Hz, 1H), 7.64 (d, J = 8.7 Hz, 1H), 7.37 (dd, J = 8.7, 2.4 Hz, 1H), 6.83 (s, 1H), 4.57 (dt, J = 12.0, 6.0 Hz, 1H), 3.14 (d, J = 12.2 Hz, 2H), 2.77 (m, 3H), 2.06 (s, 3H), 1.72−1.56 (m, 4H), 1.27 (d, J = 6.0 Hz, 6H). 13…”
Section: -Chloro-n 2 -(3-chlorophenyl)-n 4 -(2-isopropoxy-5-methyl-4-...mentioning
confidence: 99%
See 2 more Smart Citations